Development and validation of a questionnaire for the assessment of the knowledge, management and reporting ADR in paediatrics by healthcare teams (QUESA-P) - Luciane Cruz Lopes; Sheilla S Tavares; Luciane N Cruz; Juliana Castro (BMJ Open)
Objective We aimed to develop and validate a new instrument called Questionnaire for the assessment of the knowledge, management and reporting ADR in Paediatrics by Healthcare teams (QUESA-P).Design This is a cross-sectional study.Settings and participants Teams of healthcare professionals (HCP) that lead with pharmacological therapy in Paediatrician’s sector (Paediatric-HCP) in seven public hospitals in Brazil.Outcome An assessment of the knowledge and current management of ADR in Paediatric-HCP.Methods We developed and validated QUESA-P, using a standardised procedure which included item development and psychometric prevalidation using Cronbach’s Alpha, item-total correlation and test–retest validity for internal consistency and reliability. External criterion was used as criterion validation (the instrument was applied to the focus group expert vs focus group team of Paediatric-HCP in hospitals). The focus group of experts who participated in psychometrics was asked to respond to the QUESA-P twice in order to assess test-retest reliability. The content validity of the initial questionnaire was assessed by the Delphi method and pilot test. Subsequently, we made minor revisions and finalized the QUESA-PResults Selection of domains and facets were based on literature review made in duplicate by authors. Content validity was done by trial of different examiners (panellists, n=16), conducting analysis through Delphi method (three rounds). The QUESA-P was constructed with three domains. The intraclass correlations (0.80) and the Cronbach’s alpha coefficient (0.82), indicated adequate test–retest reliability and internal consistency for each domain. The application of the QUESA to 61 Paediatric-HCP in hospital resulted in lower mean score of 42.1 ± 3.4 in all domains when compared with expert teams (n= 46) 48.2 ± 3.7 (p <0.001) indicating that the instrument is valid to discriminate QUESA experts and Paediatric-HCP.Conclusion The selected domains can be used to check weaknesses in the identification, management and reporting of suspected ADR by Paediatric-HCP in Brazil.